(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2018)
The Dialogical Turn: A Review Essay of Peacebuilding Through Dialogue: Education, Human Transformation, and Conflict Resolution Edited by Peter N. Stearns, George Mason University Press, Fairfax, VA, 2018. Developed in association with the Ikeda Center for Peace, Learning, and Dialogue. ISBN : 978-1-942695-11-0 (trade paper) ISBN : 978-1-942695-12-7 (ebook)